Stenotrophomonas maltophilia Meningitis in a Term Healthy Neonate: A Case Report and Literature Review - Judy Ibrahim; Nadia Hamwi; Hala Rabei; Mohamed Abdelghafar; Zahraa Al-Dulaimi; Hossam Al Tatari (Hindawi Limited, 2018)
Stenotrophomonas maltophilia is an environmental bacterium of growing concern due to its multidrug resistance and pathogenic potential. It is considered an opportunistic pathogen of nosocomial origin most of the time, targeting a specific patients' population. We describe a case of a previously healthy full-term neonate who was found to have S. maltophilia meningitis and was successfully treated with a combination of Trimethoprim-Sulfamethoxazole and Ciprofloxacin.